2019
DOI: 10.1055/a-0858-9796
|View full text |Cite
|
Sign up to set email alerts
|

Closure of non-healing gastrocutaneous fistula after percutaneous endoscopic gastrostomy by endoscopic submucosal dissection and over-the-scope clip

Abstract: Fig. 1 Endoscopic images during endoscopic submucosal dissection of a persistent gastrocutaneous fistula after percutaneous endoscopic gastrostomy (PEG) removal showing: a the internal orifice of the fistula (arrow); bd the progressive dissection of the mucosal patch surrounding the fistula until complete ablation of the gastric mucosa. Gay-Chevallier Servane et al. Post-PEG gastrocutaneous fistula closure by ESD and OTSC … Endoscopy 2019; 51: E125-E126 E125 This document was downloaded for personal use only. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Induration and epithelialization of the tract are well known to diminish fistula healing [16]. Various attempts for de-epithelialization to promote fistula healing, such as surgical excision [16], argon plasma coagulation [17], and endoscopic submucosal dissection [18], have been reported. Conversely, it has been reported that thermal injury and mechanical trauma to the fistula may not contribute to OTSC use due to its transmural closure effects [11].…”
Section: Discussionmentioning
confidence: 99%
“…Induration and epithelialization of the tract are well known to diminish fistula healing [16]. Various attempts for de-epithelialization to promote fistula healing, such as surgical excision [16], argon plasma coagulation [17], and endoscopic submucosal dissection [18], have been reported. Conversely, it has been reported that thermal injury and mechanical trauma to the fistula may not contribute to OTSC use due to its transmural closure effects [11].…”
Section: Discussionmentioning
confidence: 99%
“…62 Once diagnosed, endoscopic approach, using endo clips to close the fistula is first choice, if it fails, surgery is necessary. 63…”
Section: Fistula Formationmentioning
confidence: 99%
“…Nevertheless, large studies evaluating those methods are lacking and long-term resolution of chronic fistulas was obtained in less than 50% of cases [8,9]. Therefore, as previously proposed in case reports [10][11][12][13][14][15], we combined two approaches with both Endoscopic submucosal dissection (ESD) of the surrounding mucosa in order to promote healing combined with clip closure into the submucosal space to increase the chances of tight healing (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, as previously proposed in case reports [10][11][12][13][14][15], we combined two techniques: endoscopic submucosal dissection (ESD) of the surrounding mucosa in order to promote healing, combined with clip closure into the submucosal space (FESDC) to increase the chances of tight healing (▶ Fig. 1).…”
Section: Introductionmentioning
confidence: 99%